Gel de doxiciclina encapsulada em ß-ciclodextrina como agente tópico adjuvante para o tratamento não cirúrgico da periodontite crônica: um ensaio clínico randomizado - Vivianne Carvalho da Cunha (2017)
Doxycycline gel encapsulated in -cyclodextrin as adjunctive topical agent for the treatment non surgical of chronic periodontitis: a randomized clinical trial. Aim: to compare the clinical efficacy of 10% doxycycline encapsulated in -cyclodextrin (DOX)/CD) in gel with 10% DOX- pure gel along adjuvants with scaling and root planning (SRP) in a clinical trial. Materials and Methods: Thirty-three subjects with diagnosis of chronic periodontitis (CP) were randomized into: group I (GI) (10% DOX gel + SRP), group II (GII) (10% DOX / -CD gel + SRP) that received application of the gels at T0 and T1, and group III (GIII), only SRP. The clinical parameters of Periodontal Probing Depth (PPD), Clinical Attachment Level (CAL), Bleeding on Probing (BOP) and Visible Plaque Index (VPI) were evaluated at baseline (T0), 30 days (T1) and 60 days (T2). Results: Within the groups, GII presented the most significant reduction in the mean of PPD and BOP and the highest mean gain in CAL (p <0.05). When comparing the three groups, the GII presented a greater reduction in PPD (2.62 mm) (p <0.003) and reached the greatest number of individuals with a gain of clinical attachment (2.54 mm) at T2 (p <0.003). The BOP and VPI had a strong reduction in all groups, comparing T2 with T0 (p <0.05). The VPI and BOP decreased 5 times and twice, respectively at T0 up to T1 in a similar way for all groups, without significant difference. In the comparative evaluation of the bone density obtained in the radiographic examinations of GI and GII performed at moments T0 (initial RX), T2 (RX 60 days after T0) and T Final (RX 18 months after T0), it was observed increase in bone density over time in all groups. There was a greater increase in bone density up to 60 days (TI). However, GII showed greater increase in bone density, but didnt have a significant difference in relation to the type of gel applied. Conclusion: the present study showed that the application of the 10% DOX gel included in -CD associated with SRP showed a significant improvement in periodontal clinical parameters (PPD, CAL and BOP) and VPI, in all analyzed protocols, providing additional benefits to the SRP alone. In the treated individuals, the periodontal pockets were shallower at the end of the investigation. There was an increase in bone density over time in all groups. However, GII showed a statistically significant increase in bone density between T0 and T2 times, without significant difference in relation to GI. The gel containing only 10% DOX also presented significant benefits to RAR, but smaller when compared to gel with inclusion compound (DOX / -CD). These results translate to a real gain in periodontal health. Therefore, the inclusion of locally released doxycycline into -CD may be an important chemotherapeutic adjuvant in the treatment of chronic periodontitis.